Study case of lighting system at Faculty of Electrical Engineering in UiTM Shah Alam: article / Mohd Hafiz Taib - Taib, Mohd Hafiz (2009)
It is important to note that lighting systems consume most of electrical energy supplied in a building in Malaysia. In UiTM Shah Alam, most of the fluorescent lamps always turn on 24 hours per day at the corridor site. Even though the corridor site is bright on the day light, the fluorescent lamps still turn on. These contribute to energy wastage. Other than that, some of the places use too much fluorescent lamps to light up the places and these make the places become too bright and this will contribute energy wastage because this contribute more than enough energy to light up the places. There are two ways the wastage energy can be reduced. Firstly is by estimating the number of fluorescent lights that are suitable with the places. Secondly is by using a system that can control the lighting system while maintaining a comfort and safe environment in the building. This paper will presents about a lighting system focus on fluorescent lamps at Electrical Faculty in UiTM Shah Alam especially at electrical machine lab. Also reported in this paper is a control system that can control the lighting system in UiTM Shah Alam.